Determinación del espesor óptico de aerosol en la Estación Antártica Peruana Machu Picchu - Ángeles Suazo, Julio (2013)
Objectives: To determine the aerosol optical depth (AOD) during january 2007 and 2008 and february 2013, at Machu Picchu Peruvian Scientific Antarctic Station (ECAMP). Methods: The research was descriptive and comparative. The main instrument to evaluate AOD was the SP02-L solar photometer for solar direct measurements with 4 sensors centered at the wavelengths of 412, 500, 675 y 862 nm. Only were used records with solar zenith angle lower than 80º and with cloud coverage of zero 30º around the sun. These measurements were compared through the Pearson test with AOD at 550 nm from MODIS (Moderate Resolution Imaging Spectroradiometer) satellites sensors. Results: It was determined a maximum and minimum mean of AOD at 0,1061 and 0,0616 respectively. It was reported a correlation coefficient with the MODIS sensor, in both the Aqua and Terra satellites, being 0,0284 and 0,0059 (p<0,05) respectively. The same correlation was evaluated with the Aerosol Index from OMI (Ozone Monitoring Instrument) sensor resulting a higher correlation, 0,3606 (p<0,05). Comparing the resulting AOD at the ECAMP with other Antarctic stations, it was found similar values around 0,06, especially with the ones close to coastal areas like Neumayer and Aboa. Conclusions: The obtained data at ECAMP during the years 2007, 2008 and 2013 don’t evidence a significant variation regarding to the aerosol optical depth. The high values obtained at ECAMP compared with the Aboa and Neumayer stations can have its explanation in the manual measurements realized in comparison with the automatic ones from other stations. Objetivos: Determinar el espesor óptico de los aerosoles (EOA) durante los meses de enero 2007 y 2008 y febrero de 2013 en la Estación Científica Antártica Machu Picchu (ECAMP). Métodos: La investigación fue descriptiva comparativa. El principal instrumento para evaluar el EOA fue el fotómetro solar SP02-L para mediciones directas del sol con 4 sensores centrados en las longitudes de onda 412, 500, 675 y 862 nm. Solo fueron utilizados ...